The Presumption of Restraint and Implicit Law - Plaxton, Michael (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
Appellate courts have frequently held that the ambit of criminal offences is more restricted than a plain reading of their text would suggest. In doing so, they have not relied on the canon of strict construction or the doctrine of de minimis non curat lex. They have instead applied what I have elsewhere called a “presumption of restraint”—a rebuttable presumption that offences provisions should not be read in such a way that they criminalize courses of action that are widely regarded by the public as benign or laudable.Drawing on the work of Lon Fuller, I argue that the presumption of restraint is compatible with parliamentary sovereignty and purposive interpretation, and that it reflects ideas about the circumstances under which legislation is capable of providing guidance to the public.